1990
DOI: 10.1111/j.1398-9995.1990.tb00501.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the second major allergen of Japanese cedar pollen

Abstract: We isolated and characterized the second major allergen (Cry j II) from Japanese cedar pollen. We found that most patients with this pollinosis had IgE antibody to this protein in addition to IgE antibody to Cry j I; however, some sera reacted only with Cry j I or Cry j II. IgE-ELISA inhibition studies revealed that Cry j I and Cry j II had no cross-allergenicity. Cry j II did not react with anti-Cry j I monoclonal antibodies. In SDS-PAGE under a non-reducing condition, Cry j II showed a band at the 37 kDa pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
86
1
1

Year Published

1994
1994
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(90 citation statements)
references
References 5 publications
2
86
1
1
Order By: Relevance
“…The mature Cry j II protein consisted of 388 amino acid residues. It was reported that the N-terminal amino acid sequence of Cryj II was AINIFNVEKY [2]. However, our results showed that the N-terminal amino acid residue begins at arginine, located 9 residues before this sequence.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…The mature Cry j II protein consisted of 388 amino acid residues. It was reported that the N-terminal amino acid sequence of Cryj II was AINIFNVEKY [2]. However, our results showed that the N-terminal amino acid residue begins at arginine, located 9 residues before this sequence.…”
Section: Discussioncontrasting
confidence: 55%
“…Cry j I was first purified and identified in 1983 [1]. Cryj II was identified in 1990 [2] as an allergen different from Cryj I in molecular weight, antigenicity and N-terminal amino acid sequence (10 residues). Cryj I and Cryj II are present in a pollen extract at a ratio of about 4:1, and 24 of 25 patients allergic to Japanese cedar pollen showed a positive reaction to Cryj I, while 19 of the 25 patients showed a positive reaction to Cry j II by a radioallergosorbent test and a skin test [3].…”
Section: Introductionmentioning
confidence: 99%
“…Two major allergens in Japanese cedar pollen have been identiˆed as Cry j I and Cry j II. [1][2][3] CJI is a basic glycoprotein with the molecular mass of 41-45 kDa. The molecular heterogeneity may originate from the presence or absence of N-linked carbohydrate chains.…”
mentioning
confidence: 99%
“…Two major allergens from Japanese cedar pollen, Cry j 1 and Cry j 2, have been shown to cause Japanese cedar pollinosis (2,3). Cry j 1 was identified as a 41-46 kDa allergen with pectate lyase enzyme activity (2,4,5), while Cry j 2 was identified as a 45 kDa allergen with polymethylgalacturonase enzyme activity (3,(6)(7)(8).…”
mentioning
confidence: 99%
“…Cry j 1 was identified as a 41-46 kDa allergen with pectate lyase enzyme activity (2,4,5), while Cry j 2 was identified as a 45 kDa allergen with polymethylgalacturonase enzyme activity (3,(6)(7)(8). Both Cry j 1 and Cry j 2 have several isoforms that differ in their primary structures, post-translational modifications, or reactivity with antibodies (9)(10)(11).…”
mentioning
confidence: 99%